Selecion of carrier material and substrate for biofertilizer by-product containing three halophilic plant growth promoting bacteria (Burkholderia cepacia BL1-10, Bacillus megaterium ST2-9 and Bacillus aquimaris KG6-3) - Nghĩa, Nguyễn Khởi; Oanh, Nguyễn Thị Kiều (Vietnam Journal of Biotechnology, 2018)
In biofertilizer production, carriers and substrates have an important role in maintaining an efficacy of the commercial biofertilizer by-product. The aim of this study was to select the best carrier material and substrate and as well substrate’s moisture to sustainably store biofertilizer by-product containing three halophilic plant growth promoting bacterial strains. They are Bacillus aquimaris KG6-3 (KG6-1), Burkholderia sp. BL1-10 (BL1-10) and Bacillus megaterium ST2-9 (ST2-9) with a function of non-symbiosic nitrogen fixer, phosphorous solubilizing bacteria and IAA producing bacteria, respectively. All the experiments in this study were conducted under the laboratory conditions. Spent coffee ground and domestic coal ash were used as carrier materials. Besides that, rice bran, banana peel, banana flesh, cocopeat and brown sugar were used as substrate materials. The results showed that the domestic coal ash was able to sustain the highest viable cell number of ST2-9 and KG6-3 strains after 16 incubation hours whilst BL1-10 was found to be highest viable cell number in carrier material of spent coffee ground and the viable cell number of mixed inoculum including three bacterial strains was shown to be not significantly different among the three tested carrier materials. Moreover, the viable cell number of all three bacterial strains regardless of single or mixed inoculation was found to be highest during 15 weeks in rice bran substrate with 50% of moisture content. The mixed viable cell number of bacterial consortium achieved highest in the substrate containing rice bran + brown sugar (15:1, w/w) and when taking into account a comparion between two inoculation means, it was shown that the viable cell number in treatments with bacteria immobilized in domestic coal ash was always higher than that in treatments with free cell bacteria inoculation method. Thus, it was concluded that domestic coal ash and rice bran + brown sugar mixture (15:1) was the best carrier material type and substrate for biofertilizer by-product containing the three holophilic plant growth promoting bacteria and the immobilization technique to inoculate bacteria via carrier material was the best option for microbial inoculation.